Copper alloy material for heat dissipation component, and heat dissipation component

By using a copper alloy material containing high Mn content and improving its Vickers hardness, the problem of softening of copper alloy materials after bonding at high temperatures in the prior art is solved, and the high rigidity and long-term stable high heat transfer characteristics of the heat dissipation parts are achieved.

CN119677888APending Publication Date: 2025-03-21FURUKAWA ELECTRIC CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380045262.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-11
Filing Date
2023-07-10
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The copper alloy materials of existing heat dissipation parts are prone to soften during jointing at high temperatures, resulting in a decrease in heat dissipation performance, and the reaction with the hydraulic fluid will lead to an increase in internal pressure, affecting the heat dissipation effect.

Method used

A copper alloy material containing more than 3.00% and less than 18.00% Mn is used, and by increasing its Vickers hardness to more than 80, the rigidity and corrosion resistance of the material are enhanced, thereby maintaining the hardness during jointing at high temperatures and reducing reaction with the hydraulic fluid.

Benefits of technology

The copper alloy sheet after bonding at high temperatures is achieved to maintain higher rigidity, and the obtained heat dissipation parts can maintain high heat transfer characteristics stably for a long time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

Provided is a copper alloy material for heat dissipation components, which is capable of maintaining the rigidity of a copper alloy sheet material itself that is higher than that of a pure copper alloy sheet material even after a high-temperature thermal history by means of joining such as brazing and welding, and which has excellent heat dissipation performance. And the obtained heat dissipation component can stably maintain the high heat transfer characteristics over a long period of time. The copper alloy material for heat dissipation components contains from 3.00% by mass to 18.00% by mass (inclusive) of Mn, with the remainder comprising Cu and unavoidable impurities, and has a Vickers hardness (HV1) of 80 or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a copper alloy material for a heat dissipation component and a heat dissipation component made by using the copper alloy material for a heat dissipation component. Background Art

[0002] In recent years, with the high functionality and performance of electrical and electronic equipment, the amount of heat released from electrical and electronic equipment has tended to increase. In addition, as the miniaturization of electrical and electronic equipment continues to progress, the heat release density will also increase, so it is increasingly important to develop a heat dissipation component that can effectively cool the electrical and electronic equipment that has released heat. As heat dissipation components that have the function of cooling the released heat, in addition to tubular heat pipes and heat spreaders as planar heat pipes, heat sinks, sheets such as heat sinks, and housings such as shielding covers can also be listed.

[0003] Here, heat pipes and heat spreaders and other heat dissipation parts usually have a closed structure, which is formed by filling the internal space with hydraulic fluid (refrigerant) and then sealing it with reduced pressure. The internal space is formed by overlapping multiple plates made of copper-based materials and joining the outer periphery. Heat pipes and heat spreaders with such a closed structure can exert heat dissipation through evaporation and condensation of the hydraulic fluid sealed in the internal space.

[0004] It is desirable to use a material having a high thermal conductivity for these heat pipes and the heat spreader. As an example of such a material, copper-based materials such as pure copper and copper alloys are used.

[0005] As copper materials used for heat dissipation parts, copper plates or copper tubes made of pure copper (e.g., oxygen-free copper: C1020) are mostly used. In addition, as copper alloy materials used for heat dissipation parts, for example, Patent Document 1 describes a copper alloy plate for heat dissipation parts, characterized in that it contains 1.0 to 4.0 mass % of one or two of Ni and Co, 0.2 to 1.2 mass % of Si, and the ratio [Ni+Co] / [Si] of the total content of Ni and Co [Ni+Co] to the content of Si [Si] is 3.5 to 5, and the remainder is composed of Cu and unavoidable impurities, and the copper alloy plate for heat dissipation parts is heated at 850°C for 30 minutes and then water-cooled, and then after aging treatment, the 0.2% resistance is 300 MPa or more, and the thermal conductivity is 25% IACS or more, and the process of manufacturing a part of the heat dissipation parts includes a heating process to 650°C or more and an aging treatment.

[0006] [Prior Technical Literature]

[0007] (Patent Document)

[0008] Patent document 1: International Publication No. 2016 / 158390. Summary of the invention

[0009] [Technical problem to be solved by the invention]

[0010] Copper plates or copper tubes made of pure copper (e.g. oxygen-free copper: C1020) used as materials for heat dissipation parts have excellent thermal conductivity and corrosion resistance, and are also soft and easily deformable. In particular, the heat of brazing and welding applied when joining the outer periphery to form the internal space may further soften the material partially or entirely.

[0011] On the other hand, Patent Document 1 describes a copper alloy plate for heat dissipation parts, which has sufficient strength and heat dissipation performance (heat transfer characteristics) even if it is heated to more than 650°C in the manufacturing process and aging treatment is performed at the same time. However, in such a copper alloy plate for heat dissipation parts, since the elements added to the copper alloy react (corrode) with the hydraulic fluid sealed in the internal space, the gas generated by the reaction increases the internal pressure of the internal space, thereby hindering the evaporation of the hydraulic fluid, so there is a concern that the heat transfer characteristics of the heat dissipation parts obtained will gradually decrease. Therefore, a copper alloy material for heat dissipation parts is sought, which, in addition to the heating in the manufacturing process, also makes it difficult to soften the copper alloy plate material constituting the heat dissipation parts by local heating at high temperatures during brazing and welding when making the heat dissipation parts, thereby maintaining the rigidity of the copper alloy plate material itself that has been made more rigid than the pure copper alloy plate material, and the high heat transfer characteristics of the heat dissipation parts obtained can also be maintained over a long period of time.

[0012] Therefore, the present invention is made in view of the above-mentioned problems, and its purpose is to provide a copper alloy material for heat dissipation parts and heat dissipation parts made of the copper alloy material for heat dissipation parts, wherein the copper alloy material for heat dissipation parts can maintain the rigidity of the copper alloy plate itself which is more rigid than the pure copper alloy plate even after undergoing a thermal history at a high temperature (for example, above 650°C) by joining such as brazing and welding, and the high heat transfer characteristics of the heat dissipation parts obtained can also be stably maintained over a long period of time.

[0013] [Technical means to solve the problem]

[0014] The present inventors have discovered that, in a copper alloy sheet material containing 3.00 mass % or more and 18.00 mass % or less of Mn (manganese) and having the remainder being an alloy composed of Cu (copper) and unavoidable impurities, by setting the Vickers hardness (HV1) to 80 or more, the rigidity of the copper alloy material for heat dissipation parts can be improved, and even if the heat dissipation parts are manufactured by joining by welding or brazing, the joint portion will still become difficult to soften, thereby improving the rigidity of the heat dissipation parts obtained and making the heat transfer characteristics of the heat dissipation parts less likely to decrease, thereby completing the present invention.

[0015] (1) A copper alloy material for heat dissipation parts, comprising 3.00 mass % or more and 18.00 mass % or less of Mn, with the remainder being Cu and inevitable impurities, and having a Vickers hardness (HV1) of 80 or more.

[0016] (2) The copper alloy material for heat dissipation parts according to (1) above, wherein the alloy composition further contains a

[0017] 0.01 mass % to 5.00 mass % of Ni (nickel),

[0018] 0.01 mass % to 5.00 mass % of Zn (zinc),

[0019] 0.01 mass % or more and 3.00 mass % or less of Sn (tin),

[0020] 0.01 mass % to 1.00 mass % of Co (cobalt),

[0021] 0.01 mass % or more and 0.30 mass % or less of Mg (magnesium),

[0022] 0.01 mass % or more and 0.30 mass % or less of Fe (iron),

[0023] 0.01 mass % to 0.70 mass % Si (silicon),

[0024] 0.01 mass % or more and 0.30 mass % or less of Cr (chromium),

[0025] 0.01 mass % or more and 0.30 mass % or less of Ag (silver), and

[0026] At least one selected from the group consisting of 0.01 mass % or more and 0.30 mass % or less of P (phosphorus).

[0027] (3) The copper alloy material for heat dissipation parts according to (1) or (2) above, wherein, in a crystal orientation analysis performed by an EBSD method, in a cross section of the copper alloy material including an extension direction and a thickness direction, the degree of integration of crystal grains having {111} planes orthogonal to the extension direction is 3.0 or less.

[0028] (4) A heat dissipation component made of the copper alloy material described in any one of (1) to (3) above.

[0029] (5) The heat dissipation component according to (4) above, wherein the heat dissipation component is a heat pipe or a heat spreader.

[0030] (6) The heat dissipation component according to (4) or (5) above, which is made of a plurality of plate materials, wherein the plurality of plate materials are made of the copper alloy material described in any one of (1) to (3) above,

[0031] The heat dissipation component has a joint portion, which is formed by welding or brazing the ends of the plurality of plates in a state where the ends of the plurality of plates overlap each other, and

[0032] The cross section of the joint portion is measured, and the average value of the Vickers hardness (HV2) at a position corresponding to the center of the thickness of each of the plurality of plate materials constituting the joint portion is 70 or more.

[0033] [Effects of the Invention]

[0034] According to the present invention, a copper alloy material for a heat dissipation component and a heat dissipation component made using the copper alloy material for a heat dissipation component can be provided. Even if the copper alloy material for a heat dissipation component has undergone a thermal history at a high temperature (for example, above 650°C) by joining such as brazing and welding, the rigidity of the copper alloy plate itself can be maintained to achieve a higher rigidity than that of a pure copper alloy plate, and the high heat transfer characteristics of the heat dissipation component obtained can also be stably maintained over a long period of time. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] none DETAILED DESCRIPTION

[0036] Next, the embodiments of the present invention will be described. The following description is an example of the embodiments of the present invention and is not intended to limit the scope of the invention claims.

[0037] According to the copper alloy material for heat dissipation parts of the present invention, the copper alloy material for heat dissipation parts contains 3.00 mass % or more and 18.00 mass % or less of Mn, and has an alloy composition in which the remainder is composed of Cu and inevitable impurities, and has a Vickers hardness (HV1) of 80 or more.

[0038] The copper alloy material for heat dissipation parts of the present invention contains an appropriate amount of Mn and also increases the Vickers hardness (HV1) to more than 80, thereby improving the rigidity of the copper alloy material for heat dissipation parts itself, and the reactivity with the refrigerant on the surface becomes extremely low, so that the heat transfer characteristics of heat dissipation parts such as heat pipes and heat spreaders can be maintained for a long time. Furthermore, the copper alloy material for heat dissipation parts of the present invention contains an appropriate amount of Mn and also increases the Vickers hardness (HV1) to more than 80, thereby when the heat dissipation parts are made by joining by welding or brazing, the joint becomes difficult to soften, thereby improving the rigidity of the heat dissipation parts made using the copper alloy material. Therefore, by using the copper alloy material for heat dissipation parts of the present invention, a copper alloy material for heat dissipation parts and a heat dissipation part made using the copper alloy material for heat dissipation parts can be provided, which can make a heat dissipation part with high rigidity by joining by welding or brazing, and can maintain the heat transfer characteristics of the heat dissipation part for a long time.

[0039] [1] Alloy composition of copper alloy materials for heat dissipation parts

[0040] The alloy composition of the copper alloy material for heat dissipating parts of the present invention contains Mn as an essential component in a range of 3.00 mass % to 18.00 mass %.

[0041] The reasons for limiting the alloy composition of the copper alloy material for heat dissipating parts will be described below.

[0042] (Mn: 3.00 mass % or more and 18.00 mass % or less)

[0043] Mn (manganese) is an easily oxidized element. Mn contained in the copper alloy will be preferentially oxidized on the surface, thereby forming a stable Mn oxide film. This film has extremely low reactivity with the refrigerant, so it is possible to maintain the heat transfer characteristics of heat dissipation parts such as heat pipes and heat spreaders for a long time. In order to play this role, Mn preferably contains more than 3.00% by mass, more preferably contains more than 4.00% by mass, further preferably contains more than 5.00% by mass, and further preferably contains more than 7.00% by mass. In particular, from the perspective of improving the Vickers hardness of the copper alloy material, Mn preferably contains more than 5.00% by mass, and more preferably contains more than 7.00% by mass. On the other hand, if the Mn content exceeds 18.00% by mass, the melting point of the copper alloy material will be reduced to less than 1000°C, so that when exposed to high temperatures during joining, there is a possibility that the shape becomes unstable. Thus, the Mn content is set to less than 18.00%. In addition, from the viewpoint of improving the solder wettability of the copper alloy material and facilitating the assembly of heat dissipation parts using solder, the Mn content is preferably set to 15.00 mass % or less, and more preferably set to 13.00 mass % or less. In particular, from the viewpoint of further improving the solder wettability of the copper alloy material and increasing the Vickers hardness of the copper alloy material, the Mn content is more preferably set in the range of 5.00 mass % or more and 13.00 mass % or less.

[0044] <Optional Added Ingredients>

[0045] The copper alloy material for heat dissipation parts of the present invention may further contain, as an optional component, at least one component selected from the group consisting of Ni, Zn, Sn, Co, Mg, Fe, Si, Cr, Ag, and P. In particular, from the viewpoint of further improving the Vickers hardness (HV1) of the copper alloy material for heat dissipation parts, it is more preferable to contain Ni, Zn, Sn, Co, Mg, Fe, Si, Cr, Ag, and P as the optional added components.

[0046] Here, the alloy composition of the copper alloy material for heat dissipation parts of the present invention can be set to further contain at least one selected from the group consisting of 0.01 mass % to 5.00 mass % Ni, 0.01 mass % to 5.00 mass % Zn, 0.01 mass % to 3.00 mass % Sn, 0.01 mass % to 1.00 mass % Co, 0.01 mass % to 0.30 mass % Mg, 0.01 mass % to 0.30 mass % Fe, 0.01 mass % to 0.70 mass % Si, 0.01 mass % to 0.30 mass % Cr, 0.01 mass % to 0.30 mass % Ag, and 0.01 mass % to 0.30 mass % P.

[0047] (Ni in an amount of 0.01 mass % or more and 5.00 mass % or less)

[0048] Ni (nickel) is a component that has the effect of increasing the Vickers hardness (HV1) of the copper alloy material for heat dissipation parts. When this effect is to be exerted, the Ni content is preferably set to 0.01 mass% or more. On the other hand, if the Ni content exceeds 5.00 mass%, the reactivity with the hydraulic fluid (refrigerant) will increase, which tends to be undesirable for making the copper alloy material for heat dissipation parts. Therefore, the Ni content is preferably in the range of 0.01 mass% or more and 5.00 mass% or less.

[0049] (0.01 mass % to 5.00 mass % of Zn)

[0050] Zn (zinc) is a component that has the effect of increasing the Vickers hardness (HV1) of the copper alloy material for heat dissipation parts. When this effect is to be exerted, the Zn content is preferably set to 0.01 mass% or more. On the other hand, if the Zn content exceeds 5.00 mass%, the reactivity with the hydraulic fluid (refrigerant) will increase, which tends to be undesirable for making the copper alloy material for heat dissipation parts. Therefore, the Zn content is preferably in the range of 0.01 mass% or more and 5.00 mass% or less.

[0051] (0.01 mass % or more and 3.00 mass % or less of Sn)

[0052] Sn (tin) is a component that has the effect of increasing the Vickers hardness (HV1) of the copper alloy material for heat dissipation parts. When this effect is to be exerted, the Sn content is preferably set to 0.01 mass% or more. On the other hand, if the Sn content exceeds 3.00 mass%, the reactivity with the hydraulic fluid (refrigerant) will increase, and the copper alloy material for heat dissipation parts will tend to be undesirable. Therefore, the Sn content is preferably in the range of 0.01 mass% or more and 3.00 mass% or less.

[0053] (0.01 mass % to 1.00 mass % Co)

[0054] Co (cobalt) is a component that has the effect of increasing the Vickers hardness (HV1) of the copper alloy material for heat dissipation parts. When this effect is to be exerted, the Co content is preferably set to 0.01 mass% or more. On the other hand, if the Co content exceeds 1.00 mass%, the reactivity with the hydraulic fluid (refrigerant) will increase, which will tend to be undesirable for making the copper alloy material for heat dissipation parts. Therefore, the Co content is preferably in the range of 0.01 mass% or more and 1.00 mass% or less.

[0055] (0.01 mass % or more and 0.30 mass % or less of Mg)

[0056] Mg (magnesium) is a component that has the effect of increasing the Vickers hardness (HV1) of the copper alloy material for heat dissipation parts. When this effect is to be exerted, the Mg content is preferably set to 0.01 mass% or more. On the other hand, if the Mg content exceeds 0.30 mass%, the reactivity with the hydraulic fluid (refrigerant) will increase, which tends to be undesirable for making the copper alloy material for heat dissipation parts. Therefore, the Mg content is preferably in the range of 0.01 mass% or more and 0.30 mass% or less.

[0057] (0.01 mass % or more and 0.30 mass % or less of Fe)

[0058] Fe (iron) is a component that has the effect of increasing the Vickers hardness (HV1) of the copper alloy material for heat dissipation parts. When this effect is to be exerted, the Fe content is preferably set to 0.01 mass% or more. On the other hand, if the Fe content exceeds 0.30 mass%, the reactivity with the hydraulic fluid (refrigerant) will increase, which tends to be undesirable for making the copper alloy material for heat dissipation parts. Therefore, the Fe content is preferably in the range of 0.01 mass% or more and 0.30 mass% or less.

[0059] (Si in an amount of 0.01 mass % or more and 0.70 mass % or less)

[0060] Si (silicon) is a component that has the effect of increasing the Vickers hardness (HV1) of the copper alloy material for heat dissipation parts. When this effect is to be exerted, the Si content is preferably set to 0.01 mass% or more. On the other hand, if the Si content exceeds 0.70 mass%, the reactivity with the hydraulic fluid (refrigerant) will increase, which tends to be undesirable for making the copper alloy material for heat dissipation parts. Therefore, the Si content is preferably in the range of 0.01 mass% or more and 0.70 mass% or less.

[0061] (0.01 mass % or more and 0.30 mass % or less of Cr)

[0062] Cr (chromium) is a component that has the effect of increasing the Vickers hardness (HV1) of the copper alloy material for heat dissipation parts. When this effect is to be exerted, the Cr content is preferably set to 0.01 mass% or more. On the other hand, if the Cr content exceeds 0.30 mass%, the reactivity with the hydraulic fluid (refrigerant) will increase, which tends to be undesirable for making the copper alloy material for heat dissipation parts. Therefore, the Cr content is preferably in the range of 0.01 mass% or more and 0.30 mass% or less.

[0063] (0.01 mass % to 0.30 mass % Ag)

[0064] Ag (silver) is a component that has the effect of increasing the Vickers hardness (HV1) of the copper alloy material for heat dissipation parts. When this effect is to be exerted, the Ag content is preferably set to 0.01 mass% or more. On the other hand, if the Ag content exceeds 0.30 mass%, the reactivity with the hydraulic fluid (refrigerant) will increase, and the copper alloy material for heat dissipation parts will tend to be undesirable. Therefore, the Ag content is preferably in the range of 0.01 mass% or more and 0.30 mass% or less.

[0065] (0.01 mass % or more and 0.30 mass % or less of P)

[0066] P (phosphorus) is a component that has the effect of increasing the Vickers hardness (HV1) of the copper alloy material for heat dissipation parts. When this effect is to be exerted, the P content is preferably set to 0.01 mass% or more. On the other hand, if the P content exceeds 0.30 mass%, the reactivity with the hydraulic fluid (refrigerant) will increase, which will tend to be undesirable for making the copper alloy material for heat dissipation parts. Therefore, the P content is preferably in the range of 0.01 mass% or more and 0.30 mass% or less.

[0067] (Remainder of Cu and unavoidable impurities)

[0068] The Cu alloy constituting the copper alloy material for heat dissipation parts has an alloy composition in which the remainder is composed of Cu and unavoidable impurities in addition to the above-mentioned components. In addition, the "unavoidable impurities" referred to here are allowable impurities, which are components present in the raw materials in most metal products, or components that are inevitably mixed in during the manufacturing process and are originally unnecessary components, but they are trace amounts and do not affect the characteristics of the metal products, so they are allowable. As components that can be listed as unavoidable impurities, for example: non-metallic elements such as S (sulfur), C (carbon), O (oxygen) and metal elements such as Sb (antimony) can be listed. In addition, the upper limit of the content of these components, for example, each of the above components can be set to 0.05% by mass, and the total amount of the above components can be set to 0.20% by mass.

[0069] [2] Vickers hardness of copper alloy materials for heat dissipation parts (HV1)

[0070] The copper alloy material for heat dissipation parts of the present invention has a Vickers hardness (HV1) of 80 or more. Thereby, the rigidity of the copper alloy material itself is improved, so when the heat dissipation parts are made of the copper alloy material for heat dissipation parts, the rigidity of the heat dissipation parts can also be improved. In order to exert this effect, the Vickers hardness (HV1) of the copper alloy material for heat dissipation parts is set to 80 or more, preferably to 85 or more, more preferably to 90 or more, and further preferably to 95 or more. In particular, in a copper alloy containing 3.00% by mass or more of Mn, by setting the Vickers hardness (HV1) to 80 or more, when the ends of multiple sheets of plate materials are overlapped to form a joint of the heat dissipation parts, when the heat dissipation parts are made by welding or brazing, the joint becomes difficult to soften, so the rigidity of the obtained heat dissipation parts can be improved.

[0071] The upper limit of the Vickers hardness (HV1) of the copper alloy material for heat dissipation components is not particularly limited, but can be set to 240 or less, for example, from the viewpoint of facilitating assembly of heat dissipation components.

[0072] Here, the Vickers hardness (HV1) of the copper alloy material for heat dissipation parts can be measured according to the Vickers hardness test method described in Japanese Industrial Standard JIS Z2244 (2009), for example. More specifically, it can be set to the following measurement value, which is measured when a diamond indenter is pressed on an arbitrary cross section of the copper alloy material for heat dissipation parts as a test piece, and the load (test force) at this time is set to 0.098N and the pressing time of the indenter is set to 15 seconds.

[0073] [3] The integration degree of grains with {111} planes perpendicular to the extension direction in a cross section including the extension direction and the thickness direction

[0074] In the crystal orientation analysis performed by the EBSD method, the integration degree of the grains having the {111} plane orthogonal to the extension direction in the cross section of the copper alloy material including the extension direction and the thickness direction is preferably 3.0 or less, and more preferably 2.6 or less. In particular, in the Cu-Mn alloy, <111> The orientation tends to be oriented in a direction parallel to the extension direction, that is, it tends to be oriented in a crystal plane close to the {111} plane orthogonal to the extension direction. Here, if the anisotropy of the material becomes higher relative to the direction intersecting the extension direction, the material with high anisotropy will deform unevenly due to the method of manufacturing the heat dissipation component and the configuration of the internal space of the heat dissipation component, thereby causing the oxide film on the surface to be destroyed, and the heat transfer function may be reduced. At this point, the copper alloy material for heat dissipation components of the present invention has a frequency of existence of grains having a {111} plane orthogonal to the extension direction in a cross section including the extension direction and the thickness direction, which is suppressed to less than 3.0 times relative to a structure having a completely random orientation distribution, thereby reducing the anisotropy of the orientation of the grains, and thus making it less likely to reduce the heat transfer function.

[0075] The degree of integration of crystal grains having {111} planes perpendicular to the extending direction in a cross section including the extending direction and the thickness direction can be determined from the intensity distribution of crystal orientations obtained by crystal orientation analysis using the EBSD method.

[0076] Here, the crystal orientation analysis by EBSD can be performed as follows: After mirror polishing the cross section of the copper alloy material for heat dissipation parts including the extension direction and the thickness direction to make a cross-sectional sample, it is observed using a field emission scanning electron microscope (FE-SEM) to perform EBSD measurement (Electron Back Scatter Diffraction). The area set as the measurement object in the EBSD measurement is set to a total of 0.1 mm 2 In the above, the step size during measurement was set to 0.2 μm.

[0077] Based on the measurement results of EBSD, using "OIM ANALYSIS" as data analysis software, a graph showing the intensity distribution of crystal orientation can be obtained. More specifically, using the harmonic series expansion, the series rank is set to 16, and the half width (Gaussian Half-Width) when fitting the Gaussian distribution is set to 5 to perform intensity calculation, and the obtained calculation results are placed in the EnforceOrthotropic Sample Symmetry option to perform collective organization analysis, thereby obtaining a graph showing the intensity distribution of crystal orientation. Based on the obtained graph, the integration of grains with {111} planes orthogonal to the extension direction in the cross section including the extension direction and the thickness direction can be calculated.

[0078] [4] Shape of copper alloy materials for heat dissipation parts

[0079] The shape of the copper alloy material for heat dissipation parts of the present invention is not particularly limited. From the perspective of the steps of joining by welding or brazing, and the ease of setting an internal space for sealing the hydraulic fluid and the evaporated gas in heat dissipation parts such as heat pipes and heat spreaders, a plate is preferred. Here, as with the plate, the copper alloy material formed by rolling can set the rolling direction as the extension direction. On the other hand, the copper alloy material of the present invention can also be a strip material such as a strip material, a wire material such as a flat wire material and a round wire material, and other forms in addition to the plate. In particular, the copper alloy material of the shape of the strip material and the wire material formed by drawing, drawing, and extrusion can set any one of the drawing direction, the drawing direction, and the extrusion direction as the extension direction. In this way, the copper alloy material for heat dissipation parts of the present invention is formed into a plate material, a strip material, a wire material, etc., and is used for at least the part of the heat dissipation parts facing the hydraulic fluid and the evaporated gas, that is, the heat transfer characteristics of the heat dissipation parts can be stably maintained over a long period of time. Here, as a part of the heat dissipation component facing the hydraulic fluid and the evaporated gas, in addition to a container having an internal space sealed with the hydraulic fluid, it also includes a wick structure which is arranged in the internal space and can promote the flow and evaporation of the hydraulic fluid, etc.

[0080] [5] Applications of copper alloy materials for heat dissipation parts

[0081] The copper alloy material for heat dissipation parts of the present invention is suitable for the production of heat dissipation parts. Here, as heat dissipation parts made of the above-mentioned copper alloy material for heat dissipation parts, heat dissipation parts that can dissipate or diffuse the heat generated inside electrical and electronic equipment to the outside of electrical and electronic equipment can be listed. As such heat dissipation parts, as an example, tubular heat pipes and surface heat pipes such as heat spreaders, radiators, heat sinks and other sheets, shielding covers and other shells can be listed. In particular, the copper alloy material for heat dissipation parts of the present invention is suitable for making a heat dissipation part that can exert heat dissipation by evaporation and condensation of hydraulic fluid sealed in the internal space, and can also be used to make heat pipes and heat spreaders in heat dissipation parts. These heat pipes and heat spreaders are provided with a hollow part (internal space) that is degassed and sealed with hydraulic fluid. The hydraulic fluid can transfer heat from the heat receiving part to the heat dissipating part while undergoing phase change in the hollow part while diffusing and reflowing. By using the copper alloy material for heat dissipation parts of the present invention to manufacture such heat pipes and heat spreaders, their rigidity can be improved, and the reaction (corrosion) caused by contact with hydraulic fluid becomes less likely to occur, thereby being able to stably maintain the high heat transfer characteristics of the heat pipes and heat spreaders over a long period of time.

[0082] In the heat dissipation parts made of the copper alloy material for heat dissipation parts of the present invention, in particular, heat dissipation parts such as heat spreaders and heat pipes that seal hydraulic fluid in the internal space, after overlapping plate-shaped materials made of copper alloy materials and sealing in a manner that leaves a flow channel portion of the hydraulic fluid to set the internal space, the hydraulic fluid is injected into the internal space that has been deaerated by decompression, and the flow channel used for the injection of the hydraulic fluid is flattened and sealed using a caulking jig, thereby sealing the hydraulic fluid in the internal space. Here, in order to completely seal the hydraulic fluid in the internal space, it is necessary to weld the sealing parts by welding such as laser welding and resistance welding, or brazing by pre-coating a brazing material, to set a joint part, and integrate them.

[0083] Therefore, as heat dissipation parts such as heat spreaders and heat pipes made of the copper alloy material for heat dissipation parts of the present invention, it is preferred that: they are made of multiple plate-like materials composed of copper alloy materials, and have a joint portion formed by welding or brazing in a state where the ends of the multiple plate materials overlap each other.

[0084] At this time, the cross section of the joint of the heat dissipating component is measured, and the average value of the Vickers hardness (HV2) at the position corresponding to the center of the thickness of each of the plurality of plates constituting the joint is preferably 70 or more, and more preferably 80 or more. In this regard, in the conventional oxygen-free copper, when the joint is provided in the heat dissipating component by welding or brazing, the vicinity of the joint softens when the joint is provided by welding, and the substantially entire copper alloy material softens when the joint is provided by brazing, and the Vickers hardness (HV2) at the position corresponding to the center of the thickness of the joint is reduced to less than 60, and thus, defects such as bending or breaking may occur in the subsequent steps of assembling in electrical and electronic equipment. In particular, when the joint is provided by welding, the temperature near the joint rises to about 800°C, and when the joint is provided by brazing, the substantially entire copper alloy material rises to about 650°C, and thus softens. In view of this, the copper alloy material for heat dissipation parts of the present invention has an average value of Vickers hardness (HV2) of 70 or more at a position corresponding to the center portion of the thickness of the joint. When the copper alloy materials are overlapped to form an internal space and when the hydraulic fluid is sealed in the internal space, even if a joint is provided by welding or brazing, the defect of bending or breaking of the heat dissipation parts due to softening of the copper alloy material can be reduced.

[0085] Here, the cross section of the joint of the heat dissipation component is measured, and the Vickers hardness (HV2) at the position corresponding to the central part of the thickness of each of the plurality of plates constituting the joint can be measured by the following method: in the cross section perpendicular to the joint surface of the plurality of plates constituting the joint and including the thickness direction of the plates, the Vickers hardness (HV) at the position corresponding to the central part in the thickness direction of at least any plate is measured according to the Vickers hardness test method described in, for example, Japanese Industrial Standard JIS Z2244 (2009). At this time, the load (test force) when pressing the diamond indenter can be set to 0.098N and the pressing time of the indenter can be set to 15 seconds.

[0086] [6] Example of a method for manufacturing a copper alloy material for heat dissipation parts

[0087] The above-mentioned copper alloy material for heat dissipation parts can be realized by combining and controlling the alloy composition and the manufacturing process, and the manufacturing process is not particularly limited. Among them, as an example of a manufacturing process for obtaining the copper alloy material for heat dissipation parts (the copper alloy material for heat dissipation parts can be used to make heat dissipation parts with high rigidity by joining such as brazing and welding, and can stably maintain the heat transfer characteristics of the heat dissipation parts over a long period of time), the following method can be listed.

[0088] An example of a method for producing a copper alloy material for heat dissipation parts according to the present invention is to sequentially perform at least a melting and casting step [step 1], a homogenization heat treatment step [step 2], a hot working step [step 3], a first cold working step [step 4], and a first annealing step [step 5] on a copper alloy material having the same alloy composition as the above-mentioned copper alloy material for heat dissipation parts.

[0089] (i) Melting and casting step [Step 1]

[0090] The melting and casting step [step 1] is a step of melting a copper alloy material having the same alloy composition as the above alloy composition and then casting it to produce an ingot of a specific shape (e.g., 30 mm thick, 100 mm wide, and 200 mm long). The melting and casting step [step 1] is preferably performed by melting and casting the copper alloy material in the atmosphere, in an inert gas atmosphere, or in a vacuum using a high-frequency melting furnace. In addition, the alloy composition of the copper alloy material may not always be completely consistent with the alloy composition of the copper alloy sheet material for heat dissipation parts because the added components may adhere or volatilize in the melting furnace in each step of the manufacturing process, but it still has an alloy composition that is substantially the same as the alloy composition of the copper alloy sheet material for heat dissipation parts.

[0091] (ii) Homogenization heat treatment step [step 2]

[0092] The homogenization heat treatment step [step 2] is a step of heat treating the ingot after the melting and casting step [step 1]. The heat treatment conditions in the homogenization heat treatment step [step 2] are preferably set to a heating temperature in the range of 800°C to 1000°C and a holding time at the heating temperature in the range of 1 hour to 10 hours from the viewpoint of making the composition distribution in the alloy during casting uniform.

[0093] (iii) Thermal processing step [step 3]

[0094] The hot working step [step 3] is a step in which the ingot subjected to the homogenization heat treatment step [step 2] is subjected to elongation processing such as rolling and wire drawing under heating until it reaches a specific thickness and size to produce a hot-worked material. Here, the hot working step [step 3] includes both a hot rolling step and a hot stretching (wire drawing) step. The conditions of the hot working step [step 3] are preferably a heating temperature in the range of 800°C or more and 1000°C or less, and may also be the same as the heating temperature in the homogenization heat treatment step [step 2]. In addition, the total processing rate (total compression rate) in the hot working step [step 3] is preferably 50% or more.

[0095] Here, the "processing rate" is a value expressed as a percentage by subtracting the cross-sectional area after processing from the cross-sectional area before elongation processing such as rolling and wire drawing, dividing the value by the cross-sectional area before processing and multiplying the result by 100, and can be expressed by the following formula.

[0096] [Processing rate] (%) = {([Cross-sectional area before processing] - [Cross-sectional area after processing]) / [Cross-sectional area before processing]} × 100

[0097] The hot working material of the hot working step [step 3] is preferably cooled. Here, the means for cooling the hot working material is not particularly limited. For example, from the viewpoint of not being easy to cause the roughening of the crystal grains, it is preferred to increase the cooling rate as much as possible, for example, it is preferred to use means such as water cooling.

[0098] Here, the surface of the hot-worked material after cooling can be cut by face cutting. By performing face cutting, the oxide film and defects on the surface generated in the hot working step [step 3] can be removed. The conditions of face cutting are not particularly limited as long as they are the conditions usually performed. The amount of the surface removed from the surface of the hot-worked material by face cutting can be appropriately adjusted based on the conditions of the hot working step [step 3], for example, it can be set to about 0.5 mm to 4 mm from the surface of the hot working material.

[0099] (v) First cold working step [step 4]

[0100] The first cold working step [step 4] is a step in which the hot-worked material after the hot working step [step 3] is subjected to extension processing such as rolling and wire drawing under cooling at an arbitrary processing rate that matches the thickness and size of the product. The first cold working step [step 4] includes both a cold rolling step and a cold extension (wire drawing) step. The conditions for the extension processing such as rolling and wire drawing in the first cold working step [step 4] are preferably such that the total processing rate is set to be greater than 50% and less than 90%. Here, if the total processing rate is less than 50%, an uneven crystal structure will be easily formed due to recrystallization, and therefore the obtained copper alloy material for heat dissipation parts will be easily softened due to the subsequent heat treatment step (annealing step). In addition, if the total processing rate exceeds 90%, grains having a {111} plane orthogonal to the extension direction will accumulate in the cross section including the extension direction and the thickness direction, and the copper alloy material for heat dissipation parts obtained thereby may have a concern of impairing anisotropy.

[0101] (vi) First annealing step [step 5]

[0102] The first annealing step [step 5] is an annealing step, which performs heat treatment on the cold-worked material after the first cold working step [step 4] to perform recrystallization. The heat treatment conditions in the first annealing step [step 5] are preferably: the heating temperature is in the range of 450°C to 650°C, and the holding time at the heating temperature is in the range of 30 seconds to 60 seconds. Here, when the heating temperature is less than 450°C and the holding time is less than 30 seconds, the recrystallization of the copper alloy material becomes difficult. In addition, when the heating temperature exceeds 650°C and the holding time exceeds 60 seconds, the Vickers hardness (HV1) of the copper alloy material for heat dissipation parts obtained will be reduced due to the coarsening of the grain size.

[0103] The cold working step and annealing step may be performed more than once for the cold working material after the first annealing step [step 5]. For example, the cold working step and annealing step may be performed a second time for the cold working material after the first annealing step [step 5], and the cold working step and annealing step at this time may be set as the second cold working step [step 6] and the second annealing step [step 7], respectively.

[0104] At this time, the total working rate in the second cold working step [step 6] is preferably set to 50% or more and 90% or less for the same reason as the first cold working step [step 4]. In addition, the conditions of the heat treatment in the second annealing step [step 7] are preferably set to a heating temperature in the range of 450°C or more and 650°C or less and a holding time at the heating temperature in the range of 30 seconds or more and 60 seconds or less for the same reason as the first annealing step [step 5].

[0105] Furthermore, for the cold-worked material after the second annealing step [step 7], a third cold-working step may be performed to further adjust the Vickers hardness of the copper alloy material, and the cold-working step at this time may be set as the third cold-working step [step 8]. Here, the total working rate when the third cold-working step [step 8] is performed is preferably set to 45% or less from the viewpoint of preventing the softening of the copper alloy material when the copper alloy material is joined by welding and brazing.

[0106] Although the embodiments of the present invention have been described above, the present invention is not limited to the above embodiments, but includes all aspects included in the concept of the present invention and the scope of the invention claims, and various changes can be made within the scope of the present invention.

[0107] [Example]

[0108] Next, in order to further clarify the effects of the present invention, examples of the present invention and comparative examples will be described, but the present invention is not limited to these examples of the present invention.

[0109] (Examples 1 to 18 of the present invention and comparative examples 1 to 4)

[0110] The melting and casting step [1] was performed to obtain an ingot with a thickness of 30 mm, wherein various copper alloy materials having the alloy compositions shown in Table 1 were melted and then cooled in an air atmosphere for casting. Here, among the components listed in Table 1, the optional additional components listed with a horizontal line "-" were not added to the copper-based material as a raw material.

[0111] For this ingot, a homogenization heat treatment step [step 2] is performed, which is to perform heat treatment at a heating temperature of 800°C or more and 1000°C or less and a holding time of 1 hour or more and 10 hours or less. Next, a hot working step [step 3] is performed to obtain a hot-worked material, wherein the hot working step [step 3] does not change the temperature and performs hot working along the length direction in a manner such that the total working rate becomes 65% (the thickness before working is 30 mm, and the thickness after working is 10.5 mm). Thereafter, it is cooled to room temperature by water cooling, and then face cutting is performed, which removes the oxide film formed on the surface of both sides. The thickness of the hot-worked material after face cutting is 8 mm.

[0112] The first cold working step [step 4] was performed on the hot worked material after the hot working step [step 3], in which cold working was performed along the longitudinal direction at a total working rate of 88% (thickness before working 8 mm, thickness after working 1 mm). Next, the first annealing step [step 5] was performed on the cold worked material after the first cold working step [step 4], in which heat treatment was performed at the heating temperature and holding time described in Table 1.

[0113] Furthermore, for the cold-worked material after the first annealing step [step 5], a second cold working step [step 6] was performed, in which cold working was performed along the length direction at a total working rate of 80% (thickness before working: 1 mm, thickness after working: 0.2 mm). Next, for the cold-worked material after the second cold working step [step 6] was performed, a second annealing step [step 7] was performed, in which heat treatment was performed at the heating temperature and holding time described in Table 1.

[0114] Here, for Examples 5 and 18 of the present invention, the copper alloy material for heat dissipation parts was obtained as follows: the second cold working step [step 6] and the second annealing step [step 7] were not performed, and after cold working was performed in the first cold working step [step 4] in a manner to achieve a total working rate of 97.5% (thickness before working 8 mm, thickness after working 0.2 mm), heat treatment was performed in the first annealing step [step 5] at the heating temperature and holding time described in Table 1. In addition, for Examples 14 and 15 of the present invention, the total working rate in the second cold working step [step 6] was set to 66.7% (thickness before working 1 mm, thickness after working 0.333 mm), and after the second annealing step [step 7], cold working was performed in the third cold working step [step 8] in the longitudinal direction at a total working rate of 40% (thickness before working 0.333 mm, thickness after working 0.2 mm).

[0115] In addition, for Comparative Examples 1 and 2, the manufacturing method described in Patent Document 1 was followed. At this time, the hot-worked material was subjected to cold rough rolling until the target plate thickness reached 0.286 mm, a recrystallization treatment accompanied by solid solution was performed, and after precipitation annealing, cold rolling with a total processing rate of 30% was performed to complete a thickness of 0.2 mm.

[0116] In this manner, copper alloy materials for heat dissipation parts according to Examples 1 to 18 of the present invention and Comparative Examples 1 to 4 were prepared.

[0117] In addition, in Table 1, constituent components other than Cu (copper) and Mn (manganese) are recorded as optional added components. In addition, in Table 1, a horizontal line "-" is recorded in the column of the component not included in the alloy composition of the copper alloy material, which clearly indicates that the component is not included or even if the component is included, it is less than the detection limit value.

[0118] [Various measurement and evaluation methods]

[0119] The copper alloy materials for heat dissipation parts of the above-mentioned examples of the present invention and comparative examples were used to carry out the following property evaluations. The evaluation conditions for each property were as follows.

[0120] [1] Measurement and evaluation of Vickers hardness (HV1) of copper alloy materials for heat dissipation parts

[0121] For the copper alloy material for heat dissipation parts, according to the Vickers hardness test method described in Japanese Industrial Standard JIS Z2244 (2009), a cross-section sample is embedded in resin and the sample is used as the object to measure the Vickers hardness (HV1). Here, the Vickers hardness (HV1) is measured on a cross section that is orthogonal to the rolling direction (stretching direction). In addition, the load (test force) when a diamond indenter is pressed on the surface of the copper alloy material as a test piece is set to 0.098N and the pressing time of the indenter is set to 15 seconds, and the Vickers hardness (HV1) of the surface of the copper alloy material at this time is measured, and then the obtained value is set as the measured value.

[0122] For the measured Vickers hardness (HV1), the case of 90 or more is regarded as a sufficiently large value of the Vickers hardness (HV1), and the rigidity (strength) of the copper alloy material constituting the heat dissipation component itself is very high, and is evaluated as "◎ (excellent)". In addition, the case of Vickers hardness (HV1) of 80 or more and less than 90 is regarded as a large value of the Vickers hardness (HV1), and the rigidity (strength) of the copper alloy material constituting the heat dissipation component itself is high, and is evaluated as "○ (good)". On the other hand, the case of Vickers hardness (HV1) of less than 80 is regarded as a small value of the Vickers hardness (HV1), and the rigidity (strength) of the copper alloy material constituting the heat dissipation component itself is low, and is evaluated as "× (poor)". In this embodiment, "◎" and "○" are evaluated as qualified grades. The results are shown in Table 2.

[0123] [2] Measurement of the integration degree and anisotropy evaluation of grains with {111} planes perpendicular to the extension direction

[0124] For the copper alloy materials for heat dissipation parts obtained in the examples of the present invention and the comparative examples, the cross-sections including the extension direction and the thickness direction were mirror-polished to prepare cross-section samples, and then observed using a field emission scanning electron microscope (FE-SEM) and EBSD measurement (measurement by electron backscatter diffraction) was performed to obtain crystal orientation analysis data by the SEM-EBSD method. Here, the area to be measured in the EBSD measurement is set to 0.1 mm in total. 2In the above, the step size during measurement is set to 0.2 μm. Based on the measurement results of EBSD, the collective organization analysis of crystal orientation is performed using "OIM ANALYSIS" as data analysis software. Using the collective organization analysis of crystal orientation of the data analysis software, the harmonic series expansion is used, the series rank is set to 16, and the half width (Gaussian Half-Width) when fitting the Gaussian distribution is set to 5゜ to perform intensity calculation, and the obtained calculation results are placed in the option of Enforce Orthotropic Sample Symmetry to perform collective organization analysis, thereby obtaining a graph showing the intensity distribution of crystal orientation. According to the obtained graph, the integration of grains having a {111} plane orthogonal to the extension direction in the cross section including the extension direction and the thickness direction can be calculated. The results are shown in Table 2.

[0125] [3] Measurement and evaluation of solder wettability

[0126] The copper alloy materials for heat dissipation parts obtained in the examples of the present invention and the comparative examples were subjected to measurement and evaluation of solder wettability as an index for facilitating assembly of heat dissipation parts using solder. Here, solder wettability was a wettability test conducted using the wetting balance method described in Japanese Industrial Standard JIS Z3198-4 "Test methods for lead-free solder - Part 4: Wettability test methods by wetting balance method and contact angle method". In the test apparatus, a solder tester SAT-5100 (manufactured by RHESCA Co., Ltd.) was used to cut a plate-shaped test piece having a thickness of 0.21 mm, a width of 10 mm, and a length of 30 mm from the obtained copper alloy material for heat dissipation parts. After applying a rosin-based flux to a position 10 mm from the end, the test apparatus was operated under the operating conditions of an immersion depth of 10 mm, an immersion speed of 10 mm / second, and an immersion time of 10 seconds in a manner perpendicular to the molten solder surface. The test piece was immersed in a Sn-Ag-Cu-based solder melted at 245°C from the end, and the time required for the solder to wet (wetting time T1) was measured.

[0127] Regarding the time required for solder wetting, when it is 8 seconds or less, the copper alloy material for heat dissipation parts is considered to have excellent solder wettability, and is evaluated as "◎ (excellent)". In addition, when the time required for solder wetting exceeds 8 seconds and is 10 seconds or less, the copper alloy material for heat dissipation parts is considered to have large and good solder wettability, and is evaluated as "○ (good)". On the other hand, when the time required for solder wetting exceeds 10 seconds, the copper alloy material for heat dissipation parts is considered to have low solder wettability, and is evaluated as "△ (acceptable)". In this embodiment, "◎" and "○" are particularly evaluated as qualified grades. The results are shown in Table 2.

[0128] [4] Measurement and evaluation of heat transfer characteristics of heat dissipation components

[0129] Using the copper alloy materials for heat dissipation components obtained in the examples of the present invention and the comparative examples, heat spreaders were produced as heat dissipation components, and the heat transfer characteristics of the obtained heat spreaders were measured.

[0130] Using three plates made of copper alloy material for heat dissipation parts with a thickness of 0.2 mm, a heat spreader was made in imitation of the first embodiment described in the gazette of Japanese Patent No. 6294981, which has a width of 40 mm and a length of 150 mm, including a flow channel and a total length of 155 mm. Here, water is used as the hydraulic fluid, and a metal mesh formed into a ladder shape when viewed from above and made of copper is used as the wick structure. In addition, the flow channel portion of the hydraulic fluid is constructed to have a width of 5 mm, a height of 5 mm, and a length of 5 mm. The hydraulic fluid is injected into the internal space of the container formed of the copper alloy material, and after the flow channel is sealed by flattening using a caulking jig, the sealing portion is completely joined by laser welding using a fiber laser to set the joint portion for integration.

[0131] Next, the obtained heat spreader was immersed in 90°C warm water at room temperature from 50 mm below the bottom in a manner that the longitudinal direction of the heat spreader became a vertical direction. A thermocouple was set on the surface at a position 10 mm below the upper end that was not immersed in warm water, and the surface temperature was measured near the upper end, which was the part corresponding to the condensation part of the heat spreader. Here, the temperature near the upper end when the temperature was fixed immediately after immersion was measured and set as the initial value. After 2000 hours from the initial state, the temperature near the upper end of the heat spreader was also measured in the same way. From the obtained measured value, the magnitude of the temperature drop after 2000 hours compared with the initial value (temperature difference) was calculated. Here, when the temperature near the upper end of the heat spreader was significantly lower than the initial value, it was considered that the hydraulic fluid sealed in the heat spreader reacted with the metal, gas was generated, and the internal pressure of the container increased, so that the heat transfer characteristics of the heat dissipation parts were reduced.

[0132] Regarding the temperature drop (temperature difference) from the initial value of the temperature near the upper end of the heat spreader after 2000 hours from the initial state, the case below 2.0°C is regarded as having excellent thermal transfer characteristics of the obtained heat dissipation component, and is evaluated as "◎ (excellent)". In addition, the case where the temperature difference exceeds 2.0°C and is below 3.0°C is regarded as having good thermal transfer characteristics of the obtained heat dissipation component, and is evaluated as "○ (good)". On the other hand, the case where the temperature difference exceeds 3.0°C is regarded as having poor thermal transfer characteristics of the obtained heat dissipation component, and is evaluated as "× (poor)". In this embodiment, "◎" and "○" are evaluated as qualified grades. The results are shown in Table 2.

[0133] [5] Measurement and evaluation of Vickers hardness (HV2) of joints

[0134] The Vickers hardness (HV2) of the heat sink parts made of the copper alloy material for heat sink parts obtained in the examples of the present invention and the comparative examples is that in the heat sink parts obtained in the same manner as in the above [4], for the joint part sealed by welding, a cross section perpendicular to the joint surface of the two sheets constituting the joint part and including the thickness direction of the sheet is embedded in resin and mirror-polished to prepare a cross-sectional sample. According to the Vickers hardness test method described in Japanese Industrial Standard JIS Z2244 (2009), the Vickers hardness (HV2) at a depth of half the thickness (0.2 mm), that is, 0.1 mm, is measured from the position corresponding to the center portion, that is, the surface of the sheet. Here, the load (test force) when a diamond indenter is pressed on the cross section of the joint part as a test piece is set to 0.098N and the pressing time of the indenter is set to 15 seconds, and the Vickers hardness (HV2) at this time is measured, and the average value of these measured values ​​is calculated.

[0135] For the average value of the measured Vickers hardness (HV2) of the joint, when it is above 80, it is considered that the value of the Vickers hardness (HV2) of the joint is sufficiently large and the copper alloy material constituting the heat dissipation component is excellent, and it is evaluated as "◎ (excellent)". In addition, when the average value of the Vickers hardness (HV2) of the joint is above 70 and less than 80, it is considered that the value of the Vickers hardness (HV2) of the joint is large and the copper alloy material constituting the heat dissipation component is good, and it is evaluated as "○ (good)". On the other hand, when the average value of the Vickers hardness (HV2) of the joint is less than 70, it is considered that the value of the Vickers hardness (HV2) of the joint is small and the copper alloy material constituting the heat dissipation component is poor, and it is evaluated as "× (poor)". In this embodiment, "◎" and "○" are evaluated as qualified grades. The results are shown in Table 2.

[0136] [6] Comprehensive evaluation

[0137] When the four evaluation results of the Vickers hardness (HV1), solder wettability, heat transfer characteristics of the heat dissipating component, and Vickers hardness (HV2) of the copper alloy material for heat dissipating parts are all evaluated as "◎ (excellent)", these four characteristics are all considered to be good and evaluated as "◎ (excellent)". In addition, when at least any one of these four characteristics is evaluated as "○" and the others are evaluated as "◎", these four characteristics are at least good and evaluated as "○ (good)". In addition, when the three evaluation results of Vickers hardness (HV1), heat transfer characteristics of the heat dissipating component, and Vickers hardness (HV2) of the joint are all evaluated as "◎" or "○" and the solder wettability is evaluated as "△", even if the Vickers hardness (HV1), heat transfer characteristics of the heat dissipating component, and Vickers hardness (HV2) of the joint are at least good, the solder wettability is considered to be poor and evaluated as "△ (fair)". On the other hand, if at least any one of the three evaluation results of Vickers hardness (HV1), heat transfer characteristics of heat dissipation parts, and Vickers hardness of joints (HV2) is "×", at least one of these three characteristics is considered to be unqualified and evaluated as "× (bad)". The results are shown in Table 2.

[0138] [Table 1]

[0139]

[0140] [Table 2]

[0141]

[0142] Based on the results in Tables 1 and 2, the copper alloy materials of Examples 1 to 18 of the present invention have alloy compositions that are within the appropriate range of the present invention, and the Vickers hardness (HV1) of the copper alloy materials is all above 80. Therefore, at least the thermal transfer characteristics of the heat dissipation parts obtained and the Vickers hardness (HV2) of the joints are at the qualified level.

[0143] On the other hand, the copper alloy materials of Comparative Examples 1 and 2 do not contain Mn, and the alloy composition is outside the appropriate range of the present invention. In addition, the heat sink (heat spreader) made of the copper alloy materials of Comparative Examples 1 and 2, after 2000 hours from the initial state, the temperature drop (temperature difference) of the temperature near the upper end of the heat spreader from the initial value is outside the appropriate range of the present invention. Therefore, the heat transfer characteristics of the heat sink parts made of the copper alloy materials of Comparative Examples 1 and 2 did not reach the qualified level.

[0144] In addition, the Mn content of the copper alloy material of Comparative Example 3 is small, and the alloy composition is outside the appropriate range of the present invention. In addition, the Vickers hardness (HV1) of the copper alloy material of Comparative Example 3 is outside the appropriate range of the present invention. Therefore, the Vickers hardness (HV2) of the joint of the heat dissipation part made using the copper alloy material of Comparative Example 3 does not reach the qualified level.

[0145] Furthermore, the Vickers hardness (HV1) of the copper alloy material of Comparative Example 4 is outside the appropriate range of the present invention. Therefore, the heat sink component manufactured using the copper alloy material of Comparative Example 4 has insufficient strength and does not reach the acceptable level.

[0146] Based on these results, it was confirmed that the copper alloy material for heat dissipation parts of the present invention, when the alloy composition and the Vickers hardness (HV1) of the copper alloy material itself were within the appropriate range, at least the heat transfer characteristics of the heat dissipation parts and the Vickers hardness (HV2) of the joints obtained were at acceptable levels.

Claims

1. A copper alloy material for heat dissipation parts, comprising 3.00 mass % or more and 18.00 mass % or less of Mn, and having an alloy composition in which the remainder is composed of Cu and inevitable impurities, and The Vickers hardness (HV1) is 80 or more.

2. The copper alloy material for heat dissipation parts according to claim 1, wherein: The aforementioned alloy composition further contains 0.01 mass % or more and 5.00 mass % or less of Ni, 0.01 mass % to 5.00 mass % of Zn, 0.01 mass % to 3.00 mass % Sn, 0.01 mass % to 1.00 mass % of Co, 0.01 mass % or more and 0.30 mass % or less of Mg, 0.01 mass % or more and 0.30 mass % or less of Fe, 0.01 mass % to 0.70 mass % of Si, 0.01 mass% to 0.30 mass% of Cr, 0.01 mass % or more and 0.30 mass % or less of Ag and At least one selected from the group consisting of 0.01 mass % or more and 0.30 mass % or less of P.

3. The copper alloy material for heat dissipation parts according to claim 1, wherein: In a crystal orientation analysis performed by the EBSD method, the degree of integration of crystal grains having {111} planes perpendicular to the extending direction of the copper alloy material was 3.0 or less.

4. A heat dissipation component, which is made of the copper alloy material according to claim 1.

5. The heat dissipation component according to claim 4, wherein: The aforementioned heat dissipation component is a heat pipe or a heat spreader.

6. The heat dissipation component according to claim 4 or 5, which is made of a plurality of plates, wherein the plurality of plates are made of the copper alloy material according to any one of claims 1 to 3. The heat dissipation component has a joint portion, which is formed by welding or brazing the ends of the plurality of plates in a state where the ends of the plurality of plates overlap each other, and The cross section of the joint portion is measured, and the average value of the Vickers hardness (HV2) at a position corresponding to the center of the thickness of each of the plurality of plate materials constituting the joint portion is 70 or more.

Citation Information

Patent Citations

  • Formation of electrode for semiconductor device

    JP1987094981A

  • Copper alloy sheet for heat dissipation component, and heat dissipation component

    WO2016158390A1